An eGFP-expressing subpopulation of growth hormone secretagogue receptor cells are distinct from kisspeptin, tyrosine hydroxylase, and RFamide-related peptide neurons in mice - Smith, Jeremy T. (2013)
Ghrelin acts on the growth hormone secretagogue receptor (GHSR) in the brain to elicit changes in physiological functions. It is associated with the neural control of appetite and metabolism, however central ghrelin also affects fertility. Central ghrelin injection in rats suppresses luteinizing hormone (LH) concentrations and pulse frequency. Although ghrelin suppresses LH and regulates kisspeptin mRNA in the anteroventral periventricular/periventricular nucleus (AVPV/PeN), there is no neuroanatomical evidence linking GHSR neural circuits to kisspeptin neurons. In this study, we first determined coexpression of GHSR and GnRH neurons using a GHSR-eGFP reporter mouse line. Using dual-label immunohistochemistry, we saw no coexpression. GHSR-eGFP expressing cells were present in the AVPV/PeN and over 90% of these expressed estrogen receptor-α (ERα). Despite this, we observed no evidence of GHSR-eGFP/kisspeptin coexpressing neurons in the AVPV/PeN. To further examine the phenotype of GHSR-eGFP cells in the AVPV/PeN, we determined coexpression with tyrosine hydroxylase (TH) and showed virtually no coexpression in the AVPV/PeN (<2%). We also observed no coexpression of GHSR-eGFP and RFamide-related peptide-3 (RFRP3) neurons in the dorsomedial hypothalamic nucleus. Importantly, we observed that approximately half of the GHSR-eGFP cells in the AVPV coexpressed Ghsr mRNA (as determined by in situ hybridization) so these data should be interpreted accordingly. Although ghrelin influences the hypothalamic reproductive axis, our data using a GHSR-eGFP reporter suggests ghrelin regulates neurons expressing ERα but does not directly act on GnRH, kisspeptin, TH, or RFRP3 neurons, as little or no GHSR-eGFP coexpression was observed.